1991
DOI: 10.21236/ada247861
|View full text |Cite
|
Sign up to set email alerts
|

Well-Covered Graphs: A Survey

Abstract: D)A graph G is well-covered (or w-c) if every maximal independent set of points in G is also maximum. Clearly, this is equivalent to the property that the greedy algorithm for constructing a maximal independent set always results in a maximum independent set. Although the problem of independence number is well-known to be NP-complete, it is trivially polynomial for well-covered graphs.The concept of well-coveredness was introduced by the author in [P1] and was first discussed therein with respect to its relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 0 publications
0
58
0
Order By: Relevance
“…In general, to compute α(G) of a graph G is an NPcomplete problem (see [10]), but it is polynomial for well-covered graphs. Characterize well-covered graphs is a difficult problem and the work on well-covered graphs that has appeared in the literature has focused on certain subclasses of well-covered graphs (see [15] for the survey).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, to compute α(G) of a graph G is an NPcomplete problem (see [10]), but it is polynomial for well-covered graphs. Characterize well-covered graphs is a difficult problem and the work on well-covered graphs that has appeared in the literature has focused on certain subclasses of well-covered graphs (see [15] for the survey).…”
Section: Introductionmentioning
confidence: 99%
“…Such graphs form the so-called class W 2 (see [20]). Thus in order to characterize Gorenstein graphs we should classify the class W 2 , but this problem is also difficult (see [15]). Note that the Gorenstein property of graphs is also dependent on the characteristic of the base field k (see Proposition 2.1), so we cannot graph-theoretically characterize all Gorenstein graphs.…”
Section: Introductionmentioning
confidence: 99%
“…This notion was introduced by Plummer in [6]. Several results on the subject have been published since then, and a thorough review can be found in [5].…”
Section: Introductionmentioning
confidence: 99%
“…Such results are proved, either by means of a complete, easy (i.e., polynomial) to detect, structural characterization of well-covered graphs in the family (such characterizations are presented and reviewed in [5]), or by an explicit description of a polynomial algorithm. Lesk et al [3] developed a polynomial time algorithm to recognize graphs in which all maximal matchings are maximum.…”
Section: Introductionmentioning
confidence: 99%
“…A well-covered graph G is a member of the class W 2 if the remove any vertex of G leaves a well-covered graph with the same independence number as G (see e.g. [14]). …”
mentioning
confidence: 99%